Diuretic, Natriuretic, And Ca2+-Sparing Effect Of The Alkaloid Boldine In Rats - Steimbach, Viviane Miranda Bispo; da Silva, Ritade Cássia Vilhena; Mariano, Luísa Nathália Bolda; Zanovello, Mariana; Macarini, Anelise Felício; da Silva, Luisa Mota; de Souza, Priscila (Drug Research, 2023)
Background Previous studies indicate the renal vasodilating effects of boldine, an alkaloid found in Peumus boldus. However, its potential to induce diuresis still needs to be studied.Methods Wistar rats were used and the urine volume was noted for 8 h and further studied.Results The acute treatment at 0.1 and 0.3 mg/kg of boldine showed a diuretic, natriuretic, and Ca2+-sparing effect in rats without changing the urinary elimination of K+and Cl-. When boldine was given in combination with hydrochlorothiazide, there was an increase in urinary volume compared to the vehicle group. However, this was not different from the treatments in its isolated form. Urine Ca2+values ​​remained low but were not enhanced by this association. The excretion of Na+and Cl- was significantly increased compared to the group that received only vehicle or boldine. On the other hand, although the association of amiloride plus boldine did not result in a diuretic effect, the increase in Na+and the reduction in K+excretion were significantly potentiated. Furthermore, in the presence of the non-selective muscarinic receptor antagonist atropine, boldine showed reduced capacity to increase urinary volume, maintaining the natriuretic and Ca2+-sparing effect, besides a very evident K+-sparing action. Similar results were obtained in the presence of the non-selective cyclooxygenase inhibitor indomethacin. Furthermore, boldine showed an ex vivo antiurolithiasis activity, reducing calcium oxalate’s precipitation and crystallization.Conclusions This study reveals the diuretic, natriuretic, Ca2+-sparing, and antiurolithiatic effects of boldine, an action possibly related to muscarinic receptor activation and prostanoid generation.
Keywords: Aporphine; diuresis; natriuresis; urolithiasis; calcium oxalate